Alcohol intake and the risk of glioma: a systematic review and updated meta-analysis of observational study. Issue 8 (28th April 2023) - Shu, Long; Yu, Dan; Jin, Fubi
Abstract: The association between alcohol intake and the risk of glioma has been widely studied, but these results have yielded conflicting findings. Therefore, we conducted this systematic review and updated meta-analysis to systematically evaluate the association between alcohol intake and the risk of glioma. A systematic literature search of relevant articles published in PubMed, Web of Science, CNKI and Wan fang databases up to December 2021 was conducted. Pooled estimated of relative risk (RR) and 95 % CI were calculated using fixed-effects models. A total of eight articles with three case–control studies involving 2706 glioma cases and 2 189 927 participants were included in this meta-analysis. A reduced risk of glioma was shown for the low–moderate alcohol drinking v . non-drinking (RR = 0·87; 95 % CI (0·78, 0·97); P = 0·014). In addition, there was no evidence of an increased risk of glioma in the heavy alcohol drinking compared with non-drinking (RR = 0·89; 95 % CI (0·67, 1·18); P = 0·404). The findings suggest an inverse association between low–moderate alcohol drinking and the risk of glioma, in the absence, however, of a dose–response relationship. More prospective studies are needed to provide further insight into the association between alcohol drinking and glioma risk.